IN VITRO PLANLET INDUCTION OF TROPICAL PITCHER PLANT (NEPENTHES AMPULLARIA JACK) BY VARIOUS THIAMIN AND BENZYL AMINO PURINE CONCENTRATE - Arwinda Dinar Cryssanti; Ari Wijayani; Endah Wahyurini (Jurnal Agrivet, 2019)
Nepenthes is one of Indonesian tropical plant as a biodiversity source that endangered from its extinction. One of the effort to prevent its extinction by using plant tissue isolation method on Nepenthes multiplication are needed. This research was aimed to determine the best interaction between Thiamin and benzyl amino purine concentration on in vitro Nepenthes planlet growth, Thiamin best concentration on in vitro Nepenthes planlet growth, and benzyl amino purine best concentration on in vitro Nepenthes planlet growth. The research was conducted in Agriculture Department Biotechnology Laboratory Universitas Pembangunan Nasional “Veteran” Yogyakarta on January – April 2018. Completed Random Design method with 2 factors was used in this research. The first factor was various concentration of Thiamin with 8 ppm, 10 ppm, and 12 ppm. The second factors was various concentration of benzyl amino purine with 0,5 ppm, 1 ppm, and 1,5 ppm. Every combination was repeated 3 times. The result of this research showed that no interaction was found in every Thiamin and benzyl amino purine various concentration on in vitro Nepenthes planlet. The usage of 10 ppm Thiamin concentration (T2) produce the best results on sprout’s amount and sprout’s height. On 1 ppm of benzyl amino purine concentration produce the best result on sprout’s amount, sptout’s height, and amount of leaves.Keyword: Nepenthes, Thiamin, Benzyl Amino Purine